2008
DOI: 10.1038/modpathol.2008.57
|View full text |Cite
|
Sign up to set email alerts
|

Array comparative genomic hybridization analysis of olfactory neuroblastoma

Abstract: Olfactory neuroblastoma is an unusual neuroectodermal malignancy, which is thought to arise at the olfactory membrane of the sinonasal tract. Due to its rarity, little is understood regarding its molecular and cytogenetic abnormalities. The aim of the current study is to identify specific DNA copy number changes in olfactory neuroblastoma. Thirteen dissected tissue samples were analyzed using array comparative genomic hybridization. Our results show that gene copy number profiles of olfactory neuroblastoma sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 37 publications
1
32
3
1
Order By: Relevance
“…A recent study suggests this commonly observed duplication in ESCs results in better growth, larger colonies, increased cell survival and decreased differentiation [4]. Moreover, duplication of 20q11 is frequently found in cancer [11,12]. Several genes located in this region are thought to confer a selective advantage to the cells.…”
Section: Resultsmentioning
confidence: 97%
“…A recent study suggests this commonly observed duplication in ESCs results in better growth, larger colonies, increased cell survival and decreased differentiation [4]. Moreover, duplication of 20q11 is frequently found in cancer [11,12]. Several genes located in this region are thought to confer a selective advantage to the cells.…”
Section: Resultsmentioning
confidence: 97%
“…Another study by Guled et al with very strict morphological and immunohistochemical inclusion criteria involved 13 ONB cases [53]. Gains were more frequent than losses.…”
Section: Cytogenetic Alterationsmentioning
confidence: 99%
“…Primary mucosal melanoma characteristically exerts at high frequency c-KIT overexpression, RAS-mitogen-activated protein kinase pathway alterations, CDKN2A mutations, loss of p16 expression (mainly related to 9p21deletions) and loss of heterozygosity; contrary to cutaneous melanoma, BRAF gene mutations are uncommon in mucosal counterpart [9]. In ONB a complex pattern of gene alterations were described, although no specific mutations have been reported [10]. As the most frequent tumor of the small salivary glands, adenoid cystic carcinoma shows a wide range of genetic and molecular alterations, with possible prognostic role or with potential therapeutic implications (EGFR, TrkC/NTRK3, PI3K/AKT pathway) [11].…”
mentioning
confidence: 94%